2021
DOI: 10.1002/ppp3.10203
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the genetic contribution of maximum yield potential, spikelet development and abortion in barley

Abstract: Societal Impact Statement To feed the world's ever‐increasing population, new genetic approaches are required. Increasing the number of living spikelets is one promising way to improve grain yield. This, in turn, increases the number of spikelets per plant, thereby increasing the total yield. We present the first evidence for genetic control of alive spikelets in barley. Discovering natural variation as well as genomic regions associated with these traits will serve as a benchmark in future breeding for improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Only grain-related organs were explored in gene expression profiling research, including CAR5, 15: caryopses at 5 and 15 DPA (days post-anthesis), LEM: Lemma [6 weeks PA (post-anthesis)], LOD: Lodicule (6 weeks PA), PAL: Palea (6 weeks PA), EPI: Epidermis (4 weeks), RAC: Rachis (5 weeks PA). This approach has been recently reported by Alqudah et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 92%
“…Only grain-related organs were explored in gene expression profiling research, including CAR5, 15: caryopses at 5 and 15 DPA (days post-anthesis), LEM: Lemma [6 weeks PA (post-anthesis)], LOD: Lodicule (6 weeks PA), PAL: Palea (6 weeks PA), EPI: Epidermis (4 weeks), RAC: Rachis (5 weeks PA). This approach has been recently reported by Alqudah et al ( 2021 ).…”
Section: Methodsmentioning
confidence: 92%
“…A strong genetic association of genes involved in phytohormones such as ABA, underlying the natural variation of spikelet abortion in the upper part of the spike, was found in barley [ 45 ]. Previous studies revealed that an increased level of ABA in the apical spikelet can enhance the risk of degeneration and decrease the rate of grain filling [ 46 ].…”
Section: Discussionmentioning
confidence: 99%